Implementasi Pajak Penghasilan Pasal 21 Pada Perusahaan Galangan Kapal - Lauwrence, Miske; Fahmi, Muhammad; Heniwati, Elok (Journal of Innovation in Management, Accounting and Business, 2024)
This research focuses on the implementation of Income Tax Article 21 at PT X, especially after the introduction of Minister of Finance Regulation Number 168 of 2023. This regulation outlines new guidelines on the calculation of taxes related to employee income. The objective of this study is to assess whether PT X has accurately implemented the provisions of this regulation and challenges faced during the implementation of the new tax guidelines. This research uses qualitative and comparative methods to analyze data, including interviews and financial documents, to evaluate the compliance of PT X with the latest tax regulations. The analysis reveals discrepancies in PT X's tax practices, where transport allowance was not considered, leading to underpayment of Income Tax Article 21. While the new regulations simplify tax calculations, they also lead to higher tax withholdings, causing concerns among employees. Despite this, the regulation was generally well-received, as it eased the administrative burden for the company's tax reporting.